UMP, SCUN seal bilateral collaborations - UMP, PNC
Universiti Malaysia Pahang (UMP) fortified its international networking when it sealed a Memorandum of Understanding (MoU) with China’s South-Central University for Nationalities (SCUN) in Beijing, China, on June 1.